HUMANITY IN FLUX; ADAPTING EDUCATION TO CONTEMPORARY CHALLENGES AND NURTURING MODERN MINDS FOR TOMMORROW - Sulubara, Seri Mughni; Abidin, Zainal; Zainuddin, Zulfa; Amrizal, Amrizal (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
In this modern era, education faces various challenges that are contemporary in nature, so there is a need for new innovations in dealing with the increasingly dynamic development of the world of education. Learning Management System (LMS) consists of Google Classroom and Zoom Platform. The relevant theory related to the research entitled "Humanity in flux; Adapting Education to Contemporary Challenges and Nurturing Modern Minds for Tommorrow" is the theory of constructivism. Various ways that can be done in facing various challenges in the world of education that are contemporary in nature, is by doing distance learning. Then, modern technology such as Learning Management System (LMS) emerges as a potential solution. Learning Management System (LMS) can be done with Google Classroom and Zoom Platform. With the help of technology and the internet, we can see a potential solution to contemporary education challenges. Technology and digital with its various advanced features and functions, help to create a more inclusive and interactive learning environment, making teaching and learning more efficient and effective.